Predictive estimation of sliding bearing load-carrying capacity and tribological durability - Chernets, Myron (Strojniški vestnik, 2021)
A computational method is presented as a method for solving a plane contact problem of the theory of elasticity to determine the contact strength and tribological durability of sliding bearings. The effect of load and radial clearance on the initial contact pressures and their reduction due to wear is studied. The durability of the bearing is estimated. Qualitative and quantitative regularities of changes in contact parameters and durability from the factors under study are established. In particular, it has been shown that both contact angles and maximum contact pressures are approximately linearly dependent on the load, and the durability decreases nonlinearly with increasing load.
Keywords: contacts; drsni ležaji; durability; obraba; parametri kontakta; parametri tribokontakta; problem kontaktne obrabe; tribocontact parameters; wear; wear-contact problem